Cultured Meat As Halalan Toyyiban Food: A Maqasid Review In The Preservation Of Life (hifz An-nafs) - Reza Adnan, M.R.A; Mohd Fadzil, S.D.N; Wan Harun, M.A; Ahmad Syukran Baharuddin (Rynnye Lyan Resources, 2024)
Indexed by Scopus/MyCite